Elasticities? claro que si! an analysis of the domestic Costa Rican food demand - Valk, A.L. van der (Research Program on Sustainability in Agriculture-REPOSA, Guápiles (Costa Rica), Centro Agronómico Tropical de Investigación y Eseñanza (CATIE), Turrialba (Costa Rica), Wageningen Agricultural University, Wageningen (Países Bajos), Ministerio de Agricultura y Ganadería, San José (Costa Rica), 2014)
Tesis (Mag.Sc) -- CATIE, Turrialba (Costa Rica), 1999